2013
DOI: 10.1158/1078-0432.ccr-13-0877
|View full text |Cite
|
Sign up to set email alerts
|

The Histone Deacetylase Inhibitor Abexinostat Induces Cancer Stem Cells Differentiation in Breast Cancer with Low Xist Expression

Abstract: Purpose: Cancer stem cells (CSC) are the tumorigenic cell population that has been shown to sustain tumor growth and to resist conventional therapies. The purpose of this study was to evaluate the potential of histone deacetylase inhibitors (HDACi) as anti-CSC therapies.Experimental Design: We evaluated the effect of the HDACi compound abexinostat on CSCs from 16 breast cancer cell lines (BCL) using ALDEFLUOR assay and tumorsphere formation. We performed gene expression profiling to identify biomarkers predict… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(86 citation statements)
references
References 56 publications
(66 reference statements)
1
82
0
2
Order By: Relevance
“…For example, increased Xist levels in the brain were observed when fetal mice were exposed to diesel exhaust [28]. Similar increases in Xist expression were also found in response to HDAC inhibitor treatment for breast cancer, or chemotherapy for ovarian cancer [29,30]. These findings raised an interesting question of whether Xist can protect cell against damage.…”
Section: Discussionmentioning
confidence: 78%
“…For example, increased Xist levels in the brain were observed when fetal mice were exposed to diesel exhaust [28]. Similar increases in Xist expression were also found in response to HDAC inhibitor treatment for breast cancer, or chemotherapy for ovarian cancer [29,30]. These findings raised an interesting question of whether Xist can protect cell against damage.…”
Section: Discussionmentioning
confidence: 78%
“…It has been suggested that HDAC inhibitors may be effective in the treatment of breast cancer because of their ability to target BCSCs decreasing proliferation of ALDH1-positive cells and decreasing the formation of breast cancer mammospheres [47]. In light of all of these studies, we determined the effect of LBH589 on TNBC cell lines with BCSC properties.…”
Section: Discussionmentioning
confidence: 99%
“…HDAC inhibitors have been found to be beneficial in BC therapy, as they target BC stem cells, have anti-proliferative effects on aldehyde dehydrogenase 1 (ALDH1)-positive cells, and suppress the formation of BC mammospheres (120). Also, ALDH1 has been associated with TNBC, so ALDH1 can be used as a BC stem cell marker in TNBC (121,122).…”
Section: Hdac Inhibitors As Anti-cancer Agentsmentioning
confidence: 99%